Development paths: A case for public investment as the alternative to the Washington Consensus - Earta Lauka (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
This paper's aim is to provide a different standpoint in the development debate, by focusing on the short-sightedness of the international institutions when they propose a development agenda. Focusing on macroeconomic performance and on privatisation, they have found a solution in PPPs, which offer financing opportunities for public investment and at the same time they reduce the burden on governments budgets. As an alternative this paper proposes a model based on investment and self-dependency with combining elements from post- Keynesian theory as well as the Beijing Consensus. The model rests on the importance of SOEs to use industrial policy as a tool to achieve independence from western powers as well as to increase investment. The theoretical claims are supported by empirical analysis based on 98 developing countries over a 15 year period.
Keywords: F14; F52; O21; O25; O38; 330; development state; PPP; Washington Consensus; privatization; public investment; Beijing Consensus; SOEs